PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA BERORIENTASI SCIENTIFIC APPROACH UNTUK MENUMBUHKAN KEMAMPUAN HIGHER ORDER THINKING (HOT) POKOK BAHASAN TRIGONOMETRI PADA SISWA SMA KELAS X - Wardhani, Indah Figa; Hobri, Hobri; Oktavianingtyas, Ervin (Kadikma, 2017)
Abstract. Education is one of the factors to the nation's progress. Education is developed through oriented scientific approach. It is acapted in increasing the students thinking ability. Moreover, scientific approach is an approach that trains the students to resolve contextual problems. Therefore, the students ability in resolving the problems can make them in higher order thinking. Especially in implementation of Curriculum 2013 the Student Worksheet (LKS) can cultivate their ability of high order thinking. The purpose of this research is to describe the process and result Development of LKS oriented to scientific approach to improve the higher order thinking ability. The research her use Plomp mode 5 phases, that is preliminary investigation, design, realization, test, evaluation, revision and implementation. The quality achievement criteria of the LKS are validity, practicality and effectiveness. The results of validity data in LKS showed that 3,8 are in a good category, the result of practicality data in LKS showed that the teacher activity during the teaching and learning show is 88,46% in the first meeting, and 92,31% in the second meeting.. The result of effectiveness data in LKS is scored by 1) Student’s activity showed 79% in the first meeting, and 83, 4% in the second meeting; 2) student’s learning outcomes showed 90%; and 3) the result of the student's positive response showed 79% to 86%. Therefore, LKS can be said to be valid, practical and effective. The LKS products are oriented scientific approach with 5M stages and meet higher order thinking level. Keyword: Student Worksheet, Scientific Approach, Higher Order Thinking